A two-year surveillance in five Colombian tertiary care hospitals reveals high frequency of Non-CG258 clones of Carbapenem- Resistant Klebsiella pneumoniae with distinct clinical characteristics (2016)
ABSTRACT : The global spread of carbapenem-resistant Klebsiella pneumoniae (CR-Kp) has been largely associated with sequence type 258 (ST258) and its related variants (clonal group 258 [CG258]). Here we describe the molecular epidemiology of CR-Kp from five tertiary care hospitals in Medellín, the second largest city in Colombia. All CR-Kp-infected patients admitted from June 2012 to June 2014 were included (n 193). Patients’ clinical information was obtained from medical records. Carbapenemase KPC, VIM, IMP, NDM, and OXA-48 genes were detected by PCR. A CG258-tonB79 cluster-specific real-time PCR (targeting the multilocus sequence type [MLST] tonB79 allele), pulsed-field gel electrophoresis (PFGE), and MLST analysis were performed for typing. Remarkably, 62.2% (n 120) of isolates were from STs unrelated to CG258 (non-CG258). KPC-3 predominated in CG258 isolates (86.3%), while KPC-2 prevailed in non-CG258 isolates (75.5%) (P < 0.001). Multidrug resistance (MDR) frequency was significantly higher in CG258 strains (91.4% versus 56.1%; P < 0.001). ST512 (a single-locus variant of ST258) is the main ST in CG258 (96.3%), and isolates in this group showed closely related pulsotype and similar resistance gene profiles, suggesting the clonal spread of this strain. In contrast, high heterogeneity of STs (34/54), including eight novel STs, was found in non-CG258 isolates. Among non-CG258 isolates, ST14 (13.3%; n 16) and ST307 (14.2%; n 17) were the most frequent, and they showed distinct molecular and clinical characteristics in comparison to CG258 isolates. Our results suggest that the dissemination of carbapenem resistance in Medellín is due to heterogeneous K. pneumoniae clones, likely the result of horizontal transmission of KPC in different unrelated lineages, further highlighting the challenge in CR-Kp infection control and the need for a multifocal intervention.